One Health scientific conference: International practices and lessons learned for Vietnam – Media report - International Livestock Research Institute; Vietnam One Health Partnership (International Livestock Research Institute, 2024)
The One Health Scientific Conference, held on 16 October 2024 in Hanoi, attracted significant attention from media outlets in Vietnam. Coverage centered around Vietnam's innovative approaches to One Health and showcased key discussions, findings, and collaborations highlighted during the conference. This report highlights the media coverage received (in English and Vietnamese).